Структура та властивості полікристалів, одержаних при спіканні порошків сBN з добавками ZrN і Al в умовах високого тиску - Кріштова, О.В.; Беженар, М.П.; Божко, С.А.; Білявина, Н.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The experimental samples of superhard polycrystals was received in cBN-ZrN-Al system by sintering powders at high pressure and temperature (7,7 GPa, 2300 K). Influence of zirconium nitride quantity on structure, hardness, density, abrasive wear of the received polycrystals is studied.